On the Development of the Doctrine of Legal Personality Denial in the Insolvency of Associated Enterprises - Junwei Ding (Law and Economy, 2022)
With the increasing number of bankruptcy cases, the insolvency of associated enterprises among them has gradually attracted widespread attention. The theory of legal personality denial has entered the field of bankruptcy law from corporate law and other fields, and is mainly applied to solve the problem of bankruptcy of associated enterprises, but the legal personality denial system has greater limitations in the current judicial application in China. Through the examination of extraterritorial application, in the new Enterprise Bankruptcy Law in the future, a special chapter on the bankruptcy of associated enterprises should be established. The denial of legal personality system should be the core, mainly dealing with the abuse of legal personality and supplemented by the two major principles of substantive consolidation and equitable subordination and applied prudently. In the process, it will be continuously integrated with China’s judicial practice. The changes in the status of the three institutional principles will be considered when the legal system for the bankruptcy of associated enterprises is perfect and mature.